Результаты теплотехнических испытаний кожухотрубного газомасляного теплообменного аппарата на стенде научно-испытательного комплекса ПАО "Сумское НПО" - Борисов, Николай Анатольевич; Голубков, Олег Григорьевич; Середа, Роман Николаевич; Удод, Михаил Николаевич (НТУ "ХПИ", 2017)
Представлена конструкция газомасляного теплообменного аппарата на базе биметаллических ребристых труб с безопасным каналом и конструкция стенда для проведения теплотехнических испытаний, а также описана методика обработки результатов испытаний. Теплотехнические испытания проведены на стенде ПАО "Сумское НПО". Приведены зависимости влияния среднего логарифмического температурного напора на величину теплового потока в кожухотрубном газомасляном теплообменном аппарате, передаваемого от горячего теплоносителя к холодному, зависимости потерь давления в трубном и межтрубном пространстве аппарата в диапазоне расходов теплоносителей; приведены значения контактного термического сопротивления и термического сопротивления воздуха безопасного канала для конструкции биметаллических ребристых труб, использованных в газомасляном теплообменном аппарате.

Application of gas-oil heat exchangers (GOH) to heat up the fuel gas and cool down oil in the lubrication system of gas turbine engine of the gas blower requires safe operation of this equipment to eliminate the leakage and the mixing of actuating media and provide quick response incase of emergency. The latter is provided by the use of bimetal tubes for GOH with the safe channel (SC) connected to the automatic gas blower emergency stop system. The PJSC "Sumy Scientific and Industrial Association" has designed a prototype of the shell-&-tube GOH on the basis of bimetal ribbed tubes (BRT) with the safe channel. Therefore, the heat engineering tests of the shell-&-tube GOH based on BRT with SC are of great practical and theoretical interest and enable the generation of specific and reliable information on the prototype system. The purpose of this research was to carry outheat-engineering tests of the prototype system of shell-&-tube GOH equipped with BRT and safe channel. The obtained test data were used to plot the relationships of the influence of average logarithmic temperature pressure on the value of thermal flow transferred from the hot heat carrier to the cold heat carrier. The values of pressure loss in the tubular and intertubular zones of the heat exchanger were defined in the range of change of the flow rates of heat carriers. The values of heat resistance of the contact and those of air in the SC were obtained for the given structure of bimetal ribbed tubes used for the GOH. Heat-engineering tests allowed us to specify the mathematical model and the appropriate program used for the computation of the process of heat transfer to the GOH based on BRT with the SC.
Heat engineering test data obtained for the shell-&-tube gas-oil heat exchanger using the scientific test system of the PJSC "Sumy Scientific and Industrial Association"
Keywords: биметаллическая ребристая труба; безопасный канал; термическое сопротивление; ГМТ; газоперекачивающий аппарат; ГПА; системы горячего теплоносителя; системы холодного теплоносителя; bimetal ribbed tube; safe channel; heat resistance